Effect of manure and NPK fertilizers on growth and production of onion (Allium cepa L.) - Maisura Maisura; Mulyadi Nurdin; Muslina Muslina (Journal of Tropical Horticulture, 2019)
Fertilization is one of efforts done by farmers to increase the production and quality of onions.  This research aimed to find out the effect of manure and NPK fertilizers to the growth and production of onions. This research was conducted in Paloh Lada Village, Dewantara Sub-district, North Aceh and Agroecotechnology Laboratory, Faculty of Agriculture, Malikussaleh University from May to July 2018. This research used Randomized Block Design (RBD) Factorial. The first factor was manure (P): 15 tons/ha (P1), 20 tons/ha (P2), 25 tons/ha (P3). The second factor was NPK fertilizers (N): 150 kg/ha (N1), 200 kg/ha (N2) and 250 kg/ha (N3). The results indicated that there was high significant interaction between manure and NPK fertilizers on wet weight and dry weight of onion bulbs and also bulb yield. The application of manure significantly enhanced the wet weight and dry weight of onion bulbs and its production and it also significantly increased the plant height at 14 days after planting. The application of NPK increased the wet weight and production of onion bulbs significantly. Also, the combination application of manure 15 tons/ha and NPK fertilizers 150 kg/ha did improve the wet weight, dry weight and production of onion bulbs.